Climate Change and Post-carbon Alternatives in Transporte - Vrčon, Maja (Upravljanje trajnostnosti v oskrbovalnih verigah, 2025)
Since the first IPCC report was published in 1990, policy makers have been confronted with the major issue of climate change and its socio-economic impacts. The impact of climate change and its consequences is a complex process that raises several questions. The current shift toward a sustainable future has made various sectors, including transport, the focus of the current urgency to address climate change. Despite this, this matter remains sensitive because it directly affects the daily decisions of countless citizens. While there is no single solution to transforming the transport sector, solutions like clean energy vehicles and fairer public transport can perhaps help us achieve the ambitious goals set by the IPCC. A post-carbon future is also possible by looking back, transporting with the wind in the sails and driving cargo bikes around the city. Various social innovations and initiatives, such as community transportation and car sharing, together with lively debates about the fair distribution of public space between different traffic users, are already changing the modes of mobility in many metropolises.